EVALUASI PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN GAGAL GINJAL KRONIK (GGK) DI UNIT HEMODIALISA RSU IMELDA PEKERJA INDONESIA MEDAN - Auliafendri, Novycha; Khairiati, Rama (JIFI (Jurnal Ilmiah Farmasi Imelda), 2022)
Chronic kidney failure (CKD) is a clinical symptom caused by chronic, progressive, and irreversible kidney function disorders. The World Health Organization (2017) reports that globally, CKD occurs in more than 500 million people. According to Riskesdas (2018) the prevalence of CKD based on a doctor's diagnosis in the population aged 15 years in Indonesia is 0.38% while in North Sumatra it is 0.33%. This method replaces the work normally carried out by the kidneys, namely cleansing the blood of metabolic wastes, toxic substances, and removing accumulated water in the body. This study aims to see the pattern of use of antihypertensives in patients with chronic kidney failure in hemodialysis Imelda Indonesian Workers General Hospital Medan period 2020. This study is a descriptive observation study in which data were taken retrospectively and analyzed by descriptive statistical methods. The pattern of use of antihypertensives in CKD patients in the hemodialysis unit of Imelda RSU Indonesian Workers is mostly amlodipine 13.0%, and the most widely used combination therapy is amlodipine with valsartan 14.4%.